Service Lifetime, Storage Time, and Disposal Pathways of Electronic Equipment: A Swiss Case Study. (24th February 2017) - Thiébaud (‐Müller), Esther; Hilty, Lorenz M.; Schluep, Mathias; Widmer, Rolf; Faulstich, Martin
Summary: Product lifetime is an essential aspect of dynamic material flow analyses and has been modeled using lifetime distribution functions, mostly average lifetimes. Existing data regarding the lifetime of electronic equipment (EE) are based on diverging definitions of lifetime as well as different temporal and regional scopes. After its active use, EE is often not disposed of immediately, but remains in storage for some time. Specific data on the share of EE that is stored and the time they remain in storage are scarce. This article investigates the service lifetime, storage time, and disposal pathways of ten electronic device types, based on data from an online survey complemented by structured interviews. We distinguish between new and secondhand devices and compute histograms, averages, and medians of the different lifetimes and their change over time. The average service lifetime varies from 3.3 years for mobile phones to 10.8 years for large loudspeakers, the average storage time from 0.8 years for flat panel display televisions to 3.6 years for large loudspeakers. Most service lifetime histograms are positively skewed and show substantial differences among device types. The storage time histograms, being more similar to one another, indicate that the storage behavior is similar for most device types. The data on disposal pathways show that a large proportion of devices are stored and reused before they reach the collection scheme.